1979
DOI: 10.1021/ed056p228
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-organic biochemistry

Abstract: Fluoro-Organic BiochemistryFluoro-organic chemistry has made a significant, impact in the biomedical and health-related sciences. Although reviews cover specific areas of fluoro-organic biochemistry (1-6), this article provides a general overview of the subject and illuminates areas where further study is desirable.Chemical Carcinogenesis (7-10)The cancer-inducing properties of polynuclear aromatic compounds have been a subject of considerable interest and importance. Fluorinated carcinogenic aromatic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Animals indicated as having died were observed to die; their livers were removed immediately or within 5 to 15 minutes of death, as determined by interval observations. We measured the NAD by a polarographic recycling method (12) after extraction as described by Klingenberg (13). Niacin was measured by a microbiological assay after extraction of niacin from livers frozen in liquid nitrogen (14).…”
Section: St Paul Minnesota 55133mentioning
confidence: 99%
See 2 more Smart Citations
“…Animals indicated as having died were observed to die; their livers were removed immediately or within 5 to 15 minutes of death, as determined by interval observations. We measured the NAD by a polarographic recycling method (12) after extraction as described by Klingenberg (13). Niacin was measured by a microbiological assay after extraction of niacin from livers frozen in liquid nitrogen (14).…”
Section: St Paul Minnesota 55133mentioning
confidence: 99%
“…Reviews have been written on the role of organic fluorine in biochemistry (13), psychiatry (14), and toxicology (15,16). The fluoroorganic compounds methoxyflurane and halothane are anesthetics (17), and artificial blood contains perfluorocarbons (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The importance of organofluorides both biologically and medicinally is well recognized. 2 Recently, we reported on the reaction of xenon difluoride (XeF 2 ) with iodine (I 2 ) or N-iodosuccinimide (NIS) in the presence of alkenes and/ or aromatics, and demonstrated that iodofluorination of the alkenes and iodination of the aromatics occurred in good yield. 3 This procedure was not applicable to the reaction of XeF 2 with Br 2 or Cl 2 because these halogens reacted too rapidly with the alkenes.…”
mentioning
confidence: 99%
“…Previous articles in this Journal have given excellent introductions to synthetic methods in organofluorine chemistry (3), biochemically significant fluorinated compounds (4), and a short history on the role of fluorine in chemistry (5). This article will review briefly the advances in selective fluorination, concentrating on the use of fluoromethanes as preformed fluorocarbon units for organic synthesis,* 1 Survey of Selective Fluorlnation Processes (6) Fluorinated organic compounds have been successfully applied to a great variety of chemical and biochemical needs (2,7).…”
mentioning
confidence: 99%